Associations of current marital status and living arrangements with HIV and syphilis risk: findings from a community-based sample of men who have sex with men in China. Issue 11 (1st November 2016) - Liu, Yu; Li, Dongliang; Vermund, Sten H.; Zhang, Chen; Ruan, Yuhua; Yin, Lu; Liu, Hongjie; Amico, K. Rivet; Shao, Yiming; Qian, Han-Zhu
ABSTRACT: Chinese men who have sex with men (MSM) are disproportionally affected by HIV and sexually transmitted infections (STIs), but little is known about the role of current marital status and living arrangements in shaping their HIV/syphilis risk. A cross-sectional study was conducted among MSM in Beijing, China to assess their sociodemographic/behavioral characteristics between married and single MSM, and test the hypothesis that currently married MSM have a lower odds of being HIV- and/or syphilis-infected. Participants were recruited via short message services, peer referral, internet, and community outreach. Data collection was based on a questionnaire survey and self-report. Infection status was lab-confirmed. Multivariable logistic regression modeling was used to assess the association of marital status and living arrangement with HIV/syphilis risk. Of the 3588 MSM, infection prevalence was high (HIV = 12.7%; syphilis = 7.5%). Compared to single MSM living with their boyfriends or male sex partners, single/alone MSM and married MSM living with wives were less likely to practice condomless insertive (CIAI) or receptive (CRAI) anal intercourse with men; while married MSM living with boyfriends or male sex partner were more likely to practice CIAI and CRAI, and married MSM were more likely to practice condomless vaginal sex. Compared to men living with boyfriends/sexual partners, significantly reduced odds of being HIV-positive were seen among married MSM who were living alone (aOR: 0.52; 95%CI: 0.28, 0.94) or living with their wives (aOR: 0.53; 95%CI: 0.31, 0.89). Similarly, single MSM living alone (aOR: 0.67; 95%CI: 0.48, 0.95) and married MSM living with their wives were comparatively less likely to be syphilis-infected (aOR: 0.43; 95%CI: 0.23, 0.79). Future efforts should consider characteristics of marital status and living arrangements for designing subgroup-specific risk reduction strategies among Chinese MSM.